2011
DOI: 10.1016/j.brat.2011.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Emotion dysregulation and adolescent psychopathology: A prospective study

Abstract: Background Emotion regulation deficits have been consistently linked to psychopathology in cross-sectional studies. However, the direction of the relationship between emotion regulation and psychopathology is unclear. This study examined the longitudinal and reciprocal relationships between emotion regulation deficits and psychopathology in adolescents. Methods Emotion dysregulation and symptomatology (depression, anxiety, aggressive behavior, and eating pathology) were assessed in a large, diverse sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

36
454
7
20

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 668 publications
(517 citation statements)
references
References 109 publications
(162 reference statements)
36
454
7
20
Order By: Relevance
“…It is important to underscore the personal nature of these traumatic events, since they have been documented to lead to more severe symptoms than impersonal traumas like accidents or natural disasters (Perry et al., 1995). Studies of interpersonal early life trauma (I‐ELT) have further revealed increases in reactivity to fear‐conditioning and startle paradigms (Jovanovic et al., 2009, 2011; Ornitz & Pynoos, 1989), decreases in stress regulation (Gunnar, Frenn, Wewerka, & Van Ryzin, 2009), and impaired emotion regulation abilities (McLaughlin, Hatzenbuehler, Mennin, & Nolen‐Hoeksema, 2011). Such behavioral alterations have been associated with increased risk of developing psychopathology in adulthood (Heim & Nemeroff, 2001), especially posttraumatic stress disorder (PTSD) (Lanius, Frewen, Vermetten, & Yehuda, 2010; McKeever & Huff, 2003; Pratchett & Yehuda, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to underscore the personal nature of these traumatic events, since they have been documented to lead to more severe symptoms than impersonal traumas like accidents or natural disasters (Perry et al., 1995). Studies of interpersonal early life trauma (I‐ELT) have further revealed increases in reactivity to fear‐conditioning and startle paradigms (Jovanovic et al., 2009, 2011; Ornitz & Pynoos, 1989), decreases in stress regulation (Gunnar, Frenn, Wewerka, & Van Ryzin, 2009), and impaired emotion regulation abilities (McLaughlin, Hatzenbuehler, Mennin, & Nolen‐Hoeksema, 2011). Such behavioral alterations have been associated with increased risk of developing psychopathology in adulthood (Heim & Nemeroff, 2001), especially posttraumatic stress disorder (PTSD) (Lanius, Frewen, Vermetten, & Yehuda, 2010; McKeever & Huff, 2003; Pratchett & Yehuda, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Evidência empírica significativa tem demonstrado a importância da desregulação emocional no desenvolvimento e manutenção de diversos problemas de internalização e externalização na adolescência (Gilbert, 2012;McLaughlin, Hatzenbuehler, Mennin, & Nolen-Hoeksema, 2011;Silk et al, 2003;Zeman, Klimes-Dougan, Cassano, & Adrian, 2007).…”
Section: Regulação Emocional: Da Psicopatologia Ao Funcionamento óTimounclassified
“…Adolescentes com depressão apresentam um repertório mais restrito de estratégias de regulação emocional, usam estratégias menos eficazes (e.g., supressão emocional), ou deixam de usar estratégias adaptativas (e.g., reavaliação cognitiva) e acreditam menos na sua eficácia (Gilbert, 2012;McLaughlin et al, 2011;Yap et al, 2007). Uma meta análise recente acerca da relação entre as estratégias de regulação emocional e psicopatologia (ansiedade, depressão, perturbações do comportamento alimentar e de abuso de substâncias) verificou que, em geral, a utilização de estratégias não adaptativas (e.g., supressão emocional) está mais associada com o desenvolvimento de psicopatologia do que a utilização de estratégias adaptativas (e.g., reavaliação cognitiva).…”
Section: Regulação Emocional: Da Psicopatologia Ao Funcionamento óTimounclassified
See 1 more Smart Citation
“…났으며 [7], 적응적인 정서조절전략의 부재가 행동화를 초래하 므로 [8], 인생의 가치관이 형성되어야 하는 중요한 시기에 체 중감량에 집착한 나머지 부정적 신체상을 확립하게 한다 [9].…”
unclassified